Diagnosing the Ergonomics of IT Environment for Operators in the 4.0 Industry - Kamil WRÓBEL; Marcin BERLIK (Communications of International Proceedings, 2021)
The 4.0 Industry (I4.0) is characterized by autonomous chains of action, that implement complex functions of integrated devices and machines with a "discrete" involvement of operators. In distribution chains, there are technical objects with different properties and operating parameters, that constitute individual operational systems. During the industrial integration of individual technical objects, specific system interactions are established between the operator, interface, intelligent control, communication, diagnostic and adjustment systems, automated technological devices (ATD) and the technological process. Such interactions are the subject of diagnosis, because they significantly influence on the efficiency of the intended tasks. This generally results from the fact, that the operator who performs the intended activities does not have any direct contact with the subject of work, because the operator receives and transmits information in the system according to the feedback basis. The evaluation of the operator's labor conditions in the 4.0 Industry requires appropriate diagnostic methods, for such purpose, relating to the very high and specific requirements of the information environment, with which a men at work must face. Classical ergonomics diagnostic methods for labor conditions do not include the appropriate and precise evaluation criteria, thanks to which the measures for correct course of the information process can be demonstrated. The so modified interaction should lead to the solution eliminating time limits and ensuring the conditions for implementation of decisive tasks in the substantial and information-related area of labor system.  The verified authorial checklist project is presented in these papers. It is based on the modification of classical ergonomics diagnostic scopes.
Keywords: 4.0 Industry; diagnosing the ergonomics; 4.0 Operator; expert systems.